(untitled) (Ius Novum, 2023)
The article deals with the issue of administrative authorities’ justification of a failure to meet deadlines for handling cases in general administrative proceedings, tax proceedings and simplified complaint proceedings. To that end, the author uses the dogmatic-legal method, performs a critical analysis of the literature on the subject matter and interprets the relevant judgments of administrative courts. The aim of the article is to draw attention to the importance of correct, exhaustive and true justification of the reasons why administrative bodies procrastinate and set new deadlines for handling administrative cases. The research area has been divided into two main parts, i.e. the analysis of the correct indication of the reasons for a delay and the diagnosis of incorrect justifications for failures to handle cases on time. The author emphasises that the reasons for a failure to deal with an administrative case on time should reflect the facts concerning the case as accurately as possible, especially when a given reason is an element of an evidence-based proceeding. Criticism was levelled at reasons not related to the course of proceedings, such as staffing problems of the authority and the multitude of cases, as well as reasons stated in too general terms, such as the complicated nature of a matter. In conclusion, the author proves that precise indication of reasons for failures to handle a case within the time limits sticks to the principle of striving for objective truth and influences the general assessment of administrative bodies.